PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD PADA MATA PELAJARAN SPREADSHEET KELAS X DI SMK NEGERI 4 SURABAYA - Rahayu, Irmawati; Rochmawati (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to develop nearpod-based interactive learning media for class X spreadsheet subjects at SMK Negeri 4 Surabaya. This research uses a type of development research or Research and Development (R&D) with the ADDIE research model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The limited trial subjects of this research were 20 class X students at SMK Negeri 4 Surabaya. The results of this research show that the results of the material expert test by Lecturers at the Faculty of Economics and Business and Teachers at SMK Negeri 4 Surabaya are said to be very adequate with an average percentage of 84%, while the results of the language test by Lecturers at the Faculty of Languages and Arts are said to be very adequate with a percentage of 88%. , and the results of the media test by Lecturers at the Faculty of Education were said to be very feasible with a percentage of 93.3%. The response of class X SMK Negeri 4 Surabaya on interactive learning media developed gets an average percentage of 97.5% which is included in the category of great understanding.